The effect of process parameters on ultraviolet cured out of die bent pultrusion process. (15th March 2016) - Tena, I.; Sarrionandia, M.; Torre, J.; Aurrekoetxea, J.
Abstract: In this paper the effect of emitting intensity and pulling speed on ultraviolet (UV) cured out of die bent pultrusion process has been analysed. The curing process of the composite at the exit of the die has been characterised (kinetic model) through the analysis of the evolution of the electrical resistivity (DC sensor) of the material. Combining the studied pulling speeds and emitting intensities, the developed curing model can predict accurately the curing degree at the exit of the die of the profiles. In addition, through the analysis of the final quality of all the manufactured bent profiles in the pultrusion line, the experimental optimum process window has been defined. Indeed, in this study, the optimum process window is limited approximately to the parameters resulting in a curing degree from 5% to 12% at the non-exposed surface (at the exit of the die).